1998
DOI: 10.1097/00004872-199816050-00001
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective effect of antihypertensive drugs in essential hypertension

Abstract: Results of a number of studies evaluating nephroprotective effects of various drugs and regimens have indicated that certain agents, most notably angiotensin converting enzyme inhibitors and their combination with calcium antagonists, afford more protection than do others at similar levels of reduction of arterial pressure. Results of still other studies suggest that certain agents that exert greater nephroprotection are more efficient at controlling arterial pressure. Therefore, further data are needed before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 141 publications
0
13
0
Order By: Relevance
“…In many patients, terminal renal failure can occur despite the presence of an efficient antihypertensive drug treatment. 28,29 We suggest that such a development should be explained not only on the basis of studies of small arteries but also of large arteries, as the latter may be damaged independent of atherosclerosis and even of increased BP levels.…”
Section: Discussionmentioning
confidence: 93%
“…In many patients, terminal renal failure can occur despite the presence of an efficient antihypertensive drug treatment. 28,29 We suggest that such a development should be explained not only on the basis of studies of small arteries but also of large arteries, as the latter may be damaged independent of atherosclerosis and even of increased BP levels.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted that our study involved drugs that were deemed to offer better nephroprotection than, perhaps, other antihypertensive agents. 15 Question may be raised as to whether our finding that the renal vascular response to dipyridamole may be compromised in hypertension has any biological significance or whether it is just another marker of hypertension. We believe that the altered responses of renal vasculature to dipyridamole may be one of the first signs of renal involvement in hypertension.…”
Section: Susic Et Al Renal Vasculature and Dipyridamole In Shrmentioning
confidence: 99%
“…Achieving target blood pressure is of utmost importance for improving renal outcomes, as reduction in blood pressure is known to exert a nephroprotective effect. 3,15,16 In these patients with renal dysfunction, mean trough plasma aliskiren concentrations increased with dose and reached steady state 2-4 weeks after the start of dosing or up-titration of the dose. The results from an earlier study assessing the effects of renal impairment on pharmacokinetics of aliskiren (300 mg once daily) in patients with mild-to-moderate renal dysfunction and healthy volunteers showed that although exposure is increased by renal impairment, the increase in exposure does not correlate with the severity of renal impairment.…”
Section: Discussionmentioning
confidence: 99%